Penggunaan Vein Viewer Oleh Perawat Dalam Melakukan Tindakan Venipuncture Pada Pasien Anak - Yersi Ahzani; La Ode Abdul Rahman (Jurnal Keperawatan, 2020)
As the development of technology either vein viewer continues to develop. The use of vein viewers in hospitals helps medical personnel especially nurses to perform venipuncture. Aim of this literature review is to identify the use of vein viewers by nurses to performing venipuncture in children. This literature review uses the Sciendirect, ProQuess, Google Scholar, and IEEE Xplore databases to find journal articles that are relevant to the 2015- 2019 limits using several keywords. Result of analyzed and obtained 5 journal which related with topic of literature review about vein viewer have advantage to process of venipuncture in children. Based on these results, the authors suggest to use of vein viewers in all rooms in the hospital to perform venipuncture measures in children, and suggest conducting research for further development related to existing vein viewer devices.